Concise synthesis of (+)-deoxoprosophylline via Co(III)(salen)-catalyzed two stereocentered HKR of racemic azido epoxides - Devalankar, Dattatray A.; Sudalai, Arumugam (Tetrahedron Letters, 2012)
An efficient synthesis of (+)-deoxoprosophylline has been achieved in high optical purity (99% ee) from readily available cis-2-butene-1,4-diol. The strategy employs Co-catalyzed Hydrolytic Kinetic Resolution (HKR) of two stereocentered racemic azido epoxides and diastereoselective intramolecular reductive cyclization as key reactions. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Azido epoxide; Hydrolytic kinetic resolution; Piperidine; Wittig olefination